CHARACTERIZATION OF Pd-Fe BIMETALLIC CATALYSTS ON DIFFERENT SUPPORTS - Linares F., Th. (2010)
Pd-Fe bimetallic catalysts were studied on different supports such as Al2O3, SiO2, C, TiO2 and MgO, which were prepared by the impregnation method at a ratio of 2/1 of Pd/Fe. The characterization was performed by XRD, DTP of hydrogen, TPR, BET and TEM. The results show a high surface area, high dispersion of metals with small crystals and the presence of two types of acid centers.